2022
DOI: 10.1038/s43018-021-00326-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective multi-kinase inhibition sensitizes mesenchymal pancreatic cancer to immune checkpoint blockade by remodeling the tumor microenvironment

Abstract: Summary KRAS-mutant pancreatic ductal adenocarcinoma (PDAC) is highly immunosuppressive and resistant to targeted and immunotherapies. Among the different PDAC subtypes, basal-like mesenchymal PDAC, which is driven by allelic imbalance, increased gene-dosage and subsequent high expression levels of oncogenic KRAS, shows the most aggressive phenotype and strongest therapy resistance. Here, we perform a systematic high-throughput combinatorial drug screen and identify a synergistic interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 76 publications
2
38
0
Order By: Relevance
“…This study demonstrated promising results and better outcomes when the PARP inhibitor was combined with ipilimumab (15.4% ORR and 59.6% 6-month PFS) compared to nivolumab (7.1% ORR and 20.6% six-month PFS). In addition, novel promising targets for pharmacologic inhibition, such as heat shock protein 90 and multi-kinases, have shown the potential to sensitize immune-cold PDACs to IO therapy in preclinical studies [ 84 , 85 ]. Early studies have also demonstrated that targeting CSF1R, the CCL2-CCR2 chemokine axis, and Bruton tyrosine kinases, among many other targets, may modulate the immune milieu and could theoretically enhance ICI efficacy [ 86 , 87 , 88 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…This study demonstrated promising results and better outcomes when the PARP inhibitor was combined with ipilimumab (15.4% ORR and 59.6% 6-month PFS) compared to nivolumab (7.1% ORR and 20.6% six-month PFS). In addition, novel promising targets for pharmacologic inhibition, such as heat shock protein 90 and multi-kinases, have shown the potential to sensitize immune-cold PDACs to IO therapy in preclinical studies [ 84 , 85 ]. Early studies have also demonstrated that targeting CSF1R, the CCL2-CCR2 chemokine axis, and Bruton tyrosine kinases, among many other targets, may modulate the immune milieu and could theoretically enhance ICI efficacy [ 86 , 87 , 88 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…CREB3LI has been reported to be activated in drug resistant cell lines [57] and GLI1 knockdown has been shown to increase sensitivity to Vemurafenib [44], an approved melanoma BRAF inhibitor. Collectively, the results from these analyses suggest a co-involvement of TFs associated with both drug resistance and cell state transition in invasive disease and highlight the promise of multi-kinase targeting [58].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown treating this class of PDAC with a MEK (trametinib) inhibitor and the multi-kinase (nintedanib) inhibitor which inhibits mutant KRas signaling allowed the infiltration of cytotoxic and effector T cells, and the cells became sensitive to the immune checkpoint inhibitor PD-L1. The combined inhibitor treatment resulted in cell cycle arrest and cell death, remodeled the immunosuppressive cancer cell secretome, and sensitized the PDAC to immune checkpoint therapy [ 177 ].…”
Section: Possibility Of Treatment Of Pdac With Small Molecule Signal ...mentioning
confidence: 99%